Efektivitas Penggunaan Lampu Light Stick pada Mata Pancing Ulur untuk Penangkapan Ikan Layur di Perairan Pasongsongan Sumenep - Agus Hermansyah; Yusrudin Yusrudin; Sumaryam Sumaryam (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2026)
The purpose of this study is to determine the effectiveness of using light sticks and without lights on catching ribbonfish from the number of catches. The method used in this study is an experimental fishing method with data analysis using the T test. This study was conducted in the waters of Pasongsongan Sumenep. The results of the ribbonfish catch during 16 trips with light sticks totaled 163 fish, while those without lights totaled 67 fish. The type of ribbonfish caught was dominated by the Trichiurus lepturus species. From the catch results, a T test analysis was carried out and the results of the Paired samples test showed a sig. value (2-tailed) of 0.000 <0.05, which means there is a significant difference in the number of catches in the use of light sticks and without lights placed on the fishing hook position. This is because ribbonfish have phototactic properties towards light, in addition to searching for food more dominantly using the sense of sight.